2015
DOI: 10.3109/09546634.2015.1034068
|View full text |Cite
|
Sign up to set email alerts
|

Blister roof grafting, cultured melanocytes transplantation and non-cultured epidermal cell suspension transplantation in treating stable vitiligo: A mutual self-control study

Abstract: All the three methods are safe and effective to treat vitiligo. Future studies with larger groups are warranted to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
3
20
2
Order By: Relevance
“…27 A greater percentage of satisfactory responses was observed by Bao et al (2015) when treating patients with segmental and non-segmental vitiligo with melanocyte transplantation. 20 The authors observed 53% of the results with excellent repigmentation and 28% with good repigmentation, with noncultured cell suspension. In their study, the authors also compared three different surgical techniques, treating, in the same session, the lesion area divided into three parts (suction blistering grafting, cultured epidermal cell suspension transplantation, and noncultured cell transplantation).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…27 A greater percentage of satisfactory responses was observed by Bao et al (2015) when treating patients with segmental and non-segmental vitiligo with melanocyte transplantation. 20 The authors observed 53% of the results with excellent repigmentation and 28% with good repigmentation, with noncultured cell suspension. In their study, the authors also compared three different surgical techniques, treating, in the same session, the lesion area divided into three parts (suction blistering grafting, cultured epidermal cell suspension transplantation, and noncultured cell transplantation).…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that the three methods are safe and efficient and should be chosen according to the size and location of the lesions and available laboratory resources. 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who underwent suction blister epidermal grafting showed excellent repigmentation results and maintained persistent pigment retention at follow‐up when grafts were applied to the face or lips . Additionally, 92% of patients in the Bao et al study developed satisfactory repigmentation (>50% repigmentation) after 10 days . Li and colleagues used a modified suction blister method in 1100 patients .…”
Section: Discussionmentioning
confidence: 99%